Lethe elwesi (Moore) stat. rev., a distinct species, with description of a new subspecies from NW Yunnan, China (Lepidoptera, Nymphalidae, Satyrinae) - Lang, Song-Yun; Bozano, Gian Cristoforo (Zootaxa, 2015)
In this paper, the specific status of Lethe elwesi (Moore, 1892) stat. rev. is recovered and a new subspecies L. elwesi houjiangae Lang & Bozano ssp. nov. is described from NW Yunnan province, China. Lethe plistia Fruhstorfer, 1911 is still regarded as a subspecies of L. jalaurida (de Nicéville, 1880).